2002
DOI: 10.1258/0022215021910500
|View full text |Cite
|
Sign up to set email alerts
|

Second malignancies in early stage laryngeal carcinoma patients treated with radiotherapy

Abstract: A retrospective review of 240 patients with T1/T2 squamous cell carcinomas of the larynx was performed. Seventy-two per cent had glottic primaries, 27 per cent had supraglottic tumours and one per cent had subglottic disease. Sixty-nine per cent presented with T1 disease and 31 per cent had T2 staged tumours. All patients were treated with definitive radiotherapy between 1973 and 1997. With a median follow-up of 68 months, 68 patients (28 per cent) have developed 72 other cancers. Ten of 68 presented with sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 16 publications
5
27
1
Order By: Relevance
“…Development of SMNs has a negative impact on survival in cases of laryngeal cancer (26,27). The present study demonstrated a trend towards decreased survival in these patients, however, the majority of irradiated patients did not develop SMNs and radiotherapy improved survival in these patients.…”
Section: Discussioncontrasting
confidence: 39%
“…Development of SMNs has a negative impact on survival in cases of laryngeal cancer (26,27). The present study demonstrated a trend towards decreased survival in these patients, however, the majority of irradiated patients did not develop SMNs and radiotherapy improved survival in these patients.…”
Section: Discussioncontrasting
confidence: 39%
“…[32,33] According to the literature, the incidence of second primary malignancy in larynx cancers ranges between 11-29%. [34][35][36] In a populationbased study performed between 1986-2008, Liao et al determined that 9,996 patients out of 93,891 patients with head neck cancer (11%) had second primary malignancies. In this study, the most frequent organ associated with the second primary malignancy was the nasopharynx (39%), whereas this frequency was 14% for the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…By stipulating that recurrences have to occur within 12 months of finishing radiotherapy, second primary tumours are very unlikely to be counted as an erroneous radiotherapy recurrence. Second primary cancers are frequent in head and neck regions, occurring at a rate of 7% per year following the index case (Holland et al, 2002). In addition, we have only used pretreatment archival biopsy material in the study.…”
Section: Discussionmentioning
confidence: 99%